Current Operating Procedure (COP) for Bleomycin ElectroScleroTherapy (BEST) of low-flow vascular malformations - Muir Tobian; Wohlgemuth Walter A; Cemazar Maja; Bertino Giulia; Groselj Ales; Ratnam Lakshmi A; McCafferty Ian; Wildgruber Moritz; Gebauer Bernhard; de Terlizzi Francesca; Zanasi Alessandro; Sersa Gregor (Radiology and Oncology)
Bleomycin ElectroScleroTherapy (BEST) is a new approach in the treatment of vascular malformations. After bleomycin is administered to the malformation, electric pulses are applied to the target area to enhance the effectiveness of bleomycin. The mode of action is comparable to the effect of electrochemotherapy on tumour vasculature. For the wider and safer use of BEST in the clinical treatment of low-flow vascular malformations, this Current Operating Procedure (COP) is being prepared. It is a proposal for the clinical standardisation of BEST using the Cliniporator® as the electrical pulse generator with its associated electrodes. The electrical parameters considered in this protocol are those validated by the European Standard Operating Procedures for Electrochemotherapy (ESOPE) with the Cliniporator®.